Characterization of Mechanical Performance of Pinus Radiata Wood Impregnated with Octadecane as Phase Change Material - Garcia-Herrera, C; Vasco-Calle, D (Elsevier Ltd, 2021)
This article presents the mechanical responses of Pinus radiata wood that was impregnated with octadecane to obtain a shape-stabilized phase change material (PCM). PCMs are used as heat storage materials to reduce the temperature peaks and displace the thermal loads in an enclosed space. It is important to study the effect of PCMs on the mechanical properties of wood, since these composite materials are intended to be used as a structural materials in low-thermal-mass housing, wherein a reduction in mechanical properties can generate structural resistance problems. For this purpose, tensile and compression tests were performed in the three principle directions (longitudinal, radial, and tangential) and bending tests were performed in the longitudinal direction. These mechanical tests were carried out using non-impregnated wood and PCM-impregnated wood, which was fabricated using a double vacuum method consisting of alternately applying a vacuum and atmospheric conditions. Different impregnation yields could be visualized using computerized microtomography, and different mechanical behaviors in the three principle directions were observed; the results showed an orthotropic behavior. However, the longitudinal direction exhibited the highest mechanical resistance. In general, the statistical tests showed that the mechanical performances of the wood samples were not affected by octadecane impregnation. © 2020 Elsevier Ltd